(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2023)
Background: The permanent cessation of ovarian function and the transition of a woman from a reproductive toa nonreproductive life is defined as Menopause. This period is characterized by remarkable changes in menstruationand hormonal patterns as well as psychological and physiological symptoms. Objectives: The objectives of this study was to assess the Body-Mass Index, Waist-Hip Ratio, Submaximal Aerobic Capacity, Ankle-Brachial Index and Quality of Life using the SF-12 questionnaire among post-menopausal apartment dwelling women. Design: Descriptive Study Methods: 110 subjects meeting the inclusion and exclusion criteria were included in the study. The subjects were assessed based on the screening tools Body-Mass Index (BMI) and Waist- Hip Ratio. The outcome tools used to assess the risk of cardiovascular disease among post-menopausal apartment dwelling women were Ankle- Brachial Index (ABI), Six-Minute Walk Test (6MWT) and health related quality of life SF-12 Questionnaire. Results: Out of 110 subjects, 59 subjects had a BMI of 25-29.9 kg/m2 and 36 subjects had a BMI of ≥30 kg/m2.56 (51%) subjects had substantially higher waist- hip ratio (≥0.85 cm). 61(55.5%) subjects had mild to moderate peripheral arterial disease on left side and 67 (60.9%) subjects had mild-moderate peripheral arterial disease on right side. The range of 6MWD is between 490-900 m. The correlation between MCS 12 and PCS 12 has an intermediate poor correlation. Conclusion: The study shows that Post- Menopausal Apartment Dwelling Women are at risk of Cardiovascular Disease.